Articulated experiences : toward a radical phenomenology of contemporary social movements - Vahabzadeh, Peyman (SUNY series in the philosophy of the social sciences., 2003)
"By reexamining the very foundations of everyday acting and thinking and stepping into the open expanse of a possible transition to a postmodern era, this book presents a radical phenomenological approach to the study of contemporary social movements. It offers a theory of acting that refuses to surrender to norms and legislations and thus always intimates a mode of thinking that challenges various manifestations of ultimacy. Vahabzadeh invites us to radically rethink many basic principles that inform our lives, such as the democratic discourse, the concept of rights, liberal democratic regimes, time and epochs, oppression, acting, and the practice of sociology, in an effort to instate a reworked concept of experience in theories about social movements."--Jacket